2021
DOI: 10.1016/j.jhazmat.2020.124296
|View full text |Cite
|
Sign up to set email alerts
|

Altered fungal communities in contaminated soils from French industrial brownfields

Abstract: Polycyclic aromatic hydrocarbons (PAHs) and metals are contaminants of industrial brownfield soils. Pollutants can have harmful effects on fungi, which are major actors of soil functioning. Our objective was to highlight fungal selection following long-term contamination of soils. Fungal diversity was assessed on 30 top-soil samples from ten sites gathered in three groups with different contamination levels and physico-chemical characteristics: 1) uncontaminated controls, 2) slag heaps displaying high PAH and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Some keystone taxa proven in this study in PAHs-PTEs contamination groups have been shown to develop PAHs and PTEs removal and detoxification functions ( Tancsics et al, 2010 ; Uyar et al, 2014 ; Tan and Parales, 2019 ). For example, isolated Agaricomycetes has great potential as a biosorbent to adsorb PAHs from industrial brownfields ( Lemmel et al, 2021 ) and can be utilized for PTEs recovery from electronic-waste ( Qi et al, 2022 ). Similarly, some members of Agaricomycetes displayed active roles in mitigating the stress of combined heavy metal toxicity on surface-sterilized rape roots ( Deng Z J, et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some keystone taxa proven in this study in PAHs-PTEs contamination groups have been shown to develop PAHs and PTEs removal and detoxification functions ( Tancsics et al, 2010 ; Uyar et al, 2014 ; Tan and Parales, 2019 ). For example, isolated Agaricomycetes has great potential as a biosorbent to adsorb PAHs from industrial brownfields ( Lemmel et al, 2021 ) and can be utilized for PTEs recovery from electronic-waste ( Qi et al, 2022 ). Similarly, some members of Agaricomycetes displayed active roles in mitigating the stress of combined heavy metal toxicity on surface-sterilized rape roots ( Deng Z J, et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…As was observed in this study, Proteobacteria, Acidobacteria, and Actinobacteria were also the most dominant bacterial phyla found in chromium-contaminated soils in the Yunnan Province (China) [ 53 ]. Our brownfield site mirrored former steel industry soils from northeastern France, which reported Ascomycota as the dominant fungal phylum [ 28 ]. Furthermore, similar to our study Alphaproteobacteria and Deltaproteobacteria were abundant bacterial classes in the soils of an urban brownfield rail yard located in Jersey City, NJ [ 8 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, filamentous fungi isolated from the genera Aspergillus , Penicillium , and Fusarium show tolerance to various heavy metals (Zn, Pb, Cr, Cd, Ni, and Co) in vitro, and Alternaria specifically has been isolated for its PAH-degrading capabilities [ 26 , 27 ]. The abundances of Cryptomycota, Dothideomycetes, Preussia , and Corynespora increase in the presence of heavy metals or PAHs in contaminated soils, suggesting that these might be bioindicators of contamination [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Only few studies have assessed plant-associated microbial taxonomic diversity and community shift in hydrocarbon contaminated sites [ 10 ]. Most of the studies on endophytes and their role in association with plants focused on bacterial endophytes, but fungal communities were also significantly impacted by hydrocarbon contamination in soils [ 11 ] and in plants [ 12 ].…”
Section: Introductionmentioning
confidence: 99%